Contribution of HLA and KIR Alleles to Systemic Sclerosis Susceptibility and Immunological and Clinical Disease Subtypes - Hanson, Aimee L.; Sahhar, Joanne; Ngian, Gene-Siew; Roddy, Janet; Walker, Jennifer; Stevens, Wendy; Nikpour, Mandana; Assassi, Shervin; Proudman, Susanna; Mayes, Maureen D.; Kenna, Tony J.; Brown, Matthew A. (Frontiers in Genetics, 2022)
Systemic sclerosis (SSc) is an autoinflammatory, fibrotic condition of unknown aetiology. The presence of detectable autoantibodies against diverse nuclear antigens, as well as strong HLA associations with disease, suggest autoimmune involvement, however the links between endogenous and exogenous risk factors and SSc pathology remain undetermined. We have conducted a genetic analysis of HLA inheritance in two independent and meta-analysed cohorts of 1,465 SSc cases and 13,273 controls, including stratified association analyses in clinical and autoantibody positive subgroups of disease. Additionally, we have used patient genotypes to impute gene dosages across the KIR locus, encoding paired activating and inhibitory lymphocyte receptors for Class I HLA ligands, to conduct the largest analysis of KIR-HLA epistatic interactions in SSc to date. We confirm previous Class II HLA associations with SSc risk and report a new Class I association with haplotype HLA-B*44:03-HLA-C*16:01 at genome-wide significance (GWS). We further report statistically significant HLA associations with clinical and serological subtypes of disease through direct case-case comparison, and report a new association of HLA-DRB1*15:01, previously shown to bind topoisomerase-1 derived peptides, with anti-topoisomerase (ATA) positive disease. Finally, we identify genetic epistasis between KIRs and HLA class I ligands, suggesting genetic modulation of lymphocyte activation may further contribute to an individual’s underlying disease risk. Taken together, these findings support future functional investigation into endogenous immunological and environmental stimuli for disrupted immune tolerance in SSc.